Revolusi Digital Dalam Meningkatkan Sosial Branding Dan Pemasaran Kerajinan Rotan Untuk Kesejahteraan Umkm Di Kelurahan Meranti Pandak - Mualfah, Desti; Malindo, Qori; Gunawan, Sulka; Zacki, Moh Soulthan; Novia5, Sherlin Okta (LPPM UMRI, 2023)
In the era of globalization and technological development, new opportunities and challenges arise for Micro, Small and Medium Enterprises (MSMEs) to develop their business. This journal discusses how the digital revolution can be adopted by Meranti Pandak MSMEs in an effort to improve social branding and marketing of their rattan handicraft products to achieve sustainable prosperity. With qualitative research methods, we explore the implementation of MSME digital strategies in interacting with the market and consumers. This case study reveals how the use of social media and e-commerce platforms enables Meranti Pandak MSMEs to build a strong brand image, reach potential consumers on a larger scale, and participate in the global market. Our findings show that the combination of creativity in social branding through attractive visual content and effectiveness in digital marketing can have a positive impact on income and improve the welfare of MSMEs and surrounding communities. Nevertheless, challenges related to digital literacy and technology management remain relevant, requiring collaborative efforts between relevant parties. This research provides insight into the potential of digital revolution strategies for MSMEs and provides input for further development in supporting local economic growth.